Privacy evaluation: what empirical research on users' valuation of personal data tells us - Federico Morando; Raimondo Iemma; Emilio Raiteri (Internet Policy Review, 2014)
The EU General Data Protection Regulation is supposed to introduce several innovations, including the right of data portability for data subjects. In this article, we review recent literature documenting experiments to assess users' valuation of personal data, with the purpose to provide policy-oriented remarks. In particular, contextual aspects, conflicts between declared and revealed preferences, as well as the suggestion that personal data is not conceivable as a single good, but instead as a bundle, are taken into account, also discussing potential shortcomings and pitfalls in the surveyed experiments. Data portability is supposed to increase consumer empowerment; still, several technological preconditions need to apply to make this right actually enforceable.
Keywords: 300; Privacy; Personal data; Economic value